Extragenital Infections Caused by Chlamydia trachomatis and Neisseria gonorrhoeae: A Review of the Literature - Philip A. Chan; Ashley Robinette; Madeline Montgomery; Alexi Almonte; Susan Cu-Uvin; John R. Lonks; Kimberle C. Chapin; Erna M. Kojic; Erica J. Hardy (Hindawi Limited, 2016)
In the United States, sexually transmitted diseases due to Chlamydia trachomatis and Neisseria gonorrhoeae continue to be a major public health burden. Screening of extragenital sites including the oropharynx and rectum is an emerging practice based on recent studies highlighting the prevalence of infection at these sites. We reviewed studies reporting the prevalence of extragenital infections in women, men who have sex with men (MSM), and men who have sex only with women (MSW), including distribution by anatomical site. Among women, prevalence was found to be 0.6-35.8% for rectal gonorrhea (median reported prevalence 1.9%), 0-29.6% for pharyngeal gonorrhea (median 2.1%), 2.0-77.3% for rectal chlamydia (median 8.7%), and 0.2-3.2% for pharyngeal chlamydia (median 1.7%). Among MSM, prevalence was found to be 0.2-24.0% for rectal gonorrhea (median 5.9%), 0.5-16.5% for pharyngeal gonorrhea (median 4.6%), 2.1-23.0% for rectal chlamydia (median 8.9%), and 0-3.6% for pharyngeal chlamydia (median 1.7%). Among MSW, the prevalence was found to be 0-5.7% for rectal gonorrhea (median 3.4%), 0.4-15.5% for pharyngeal gonorrhea (median 2.2%), 0-11.8% for rectal chlamydia (median 7.7%), and 0-22.0% for pharyngeal chlamydia (median 1.6%). Extragenital infections are often asymptomatic and found in the absence of reported risk behaviors, such as receptive anal and oral intercourse. We discuss current clinical recommendations and future directions for research.